Slow Surface Eigenmodes Directed by the Mu-Negative Metamaterial Slab - Viktor Galaydych; Oleksandr Sporov; Volodymyr Olefir; Mykola Azarenkov (East European Journal of Physics, 2022)
The paper presents the results of the study of slow surface electromagnetic waves directed along the flat mu-negative metamaterial slab surrounded by ordinary dielectric material. It is considered the case of isotropic and homogeneous metamaterial without losses. This metamaterial possesses the positive permittivity and the negative permeability over a definite frequency band. It is found that two surface modes of TE polarization can propagate along such waveguide structure. The dispersion properties, the spatial distribution of the electromagnetic field, as well as the phase and group velocities of these slow modes are studied. The first mode is a conventional forward wave, and has a lower frequency and lower phase velocity than the second mode. The second mode may have zero group velocity at a certain frequency. Characteristics of these surface modes for different values of the mu-negative slab parameters have been studied. The studied surface electromagnetic waves can be used for practical applications as in laboratory experiments, as in various technologies.